English translation and validation of the Zurich chronic middle ear inventory (ZCMEI‐21‐E) assessing quality of life in chronic otitis media: A prospective international multicentre study. (14th January 2019) - Chatzimichalis, Michail; Epprecht, Lorenz; Weder, Stefan; Shaul, Chanan; Engle Folchert, Kristi J.; Machala, Maria C.; Goosmann, Madeline M.; Naville, Marc; Zhu, Angela; Röösli, Christof; Lee, Daniel J.; Cass, Stephen P.; et al.
Abstract : Objectives: To translate and validate the Zurich Chronic Middle Ear Inventory (ZCMEI‐21) for the English language in order to provide an English instrument to assess health‐related quality of life in chronic otitis media (COM). Design: Pilot translation study including cognitive debriefings, prospective multicentre cross‐sectional psychometric validation study. Setting: Four tertiary referral centres in three different English‐speaking countries (UK, USA and Australia). Participants: Adult patients suffering from COM. Main outcome measures: The English translation of the ZCMEI‐21 (ZCMEI‐21‐E) and the five‐level version of the EQ‐5D questionnaire. The EQ‐5D, which constitutes a generic measure of health‐related quality of life, consists of a descriptive system score and a visual analogue scale. Statistical outcomes included single‐item descriptive statistics, internal consistency (Cronbach's α ) as an indicator of reliability, as well as construct validity. Results: A total of 124 patients suffering from COM were included. The mean age was 50.1 years (SD 16.9 years), and 72 (58.1%) were males. The Cronbach's α of the ZCMEI‐21‐E was 0.91, suggesting an excellent internal consistency. The Spearman's correlation coefficient of the ZCMEI‐21‐E total score was 0.55 ( P < 0.0001) for convergent construct validity with EQ‐5D descriptive system score and 0.57 ( P < 0.0001) with the EQ‐5D visual analogue scale. Conclusions: The ZCMEI‐21‐E is a new validated questionnaire that provides clinicians with a short, comprehensive and reliable instrument to quantify health‐related quality of life in patients suffering from COM. The ZCMEI‐21‐E may be of use in clinical routine as well as in outcome research and monitoring.